Posterior moments and quantiles for the normal location model with Laplace prior. Issue 17 (9th August 2021) - De Luca, Giuseppe; Magnus, Jan R.; Peracchi, Franco
Abstract: We derive explicit expressions for arbitrary moments and quantiles of the posterior distribution of the location parameter η in the normal location model with Laplace prior, and use the results to approximate the posterior distribution of sums of independent copies of η .